(untitled) (Research, Society and Development, 2021)
Nutritional assessment by foliar analysis makes it possible to verify the culture’s ability to absorb nutrients, thereby allowing the diagnosis of the limiting nutritional factors for production. Thus, beans with a reduced cycle and root system predominant in the superficial layers of the soil, can benefit from this diagnosis, becoming an important tool for other cultivation cycles, with strictly local information. Thus, the objective of the work was to diagnose the most limiting nutrients and interactions in beans by the sufficiency ranges methodology. The experiment was conducted in the municipality of Montividiu-GO, using the cultivar BRSMG Madrepérola with sowing in early October. It totaled 49 samplings, a composite sample was formed by 30 subsamples, the first fully expanded leaf at the time of flowering was sampled. In the interpretation of leaf results by the sufficiency range method, the values were subjected to univariate statistical test, frequency distribution and Pearson’s linear correlation between nutrient levels. He found that sulfur is the element with the lowest absorption in common beans, with 98% of the samples being classified as deficient for the crop. The nutrients, phosphorus, potassium and manganese, in 100% of the samples were classified in excess. It was found that nitrogen, calcium and zinc were found in excess, in 51%, 85.7% and 98% of the samples, respectively. It is concluded that the sufficiency bands methodology is efficient for the interpretation of leaf results with the interest of adequacy in the nutritional management of the bean culture.